Effect of Capital Adequacy Requirement on Profitability of Selected Banks Listed on Ghana Stock Exchange - Mark Amissah; Oscar Agyemang Opoku (The Indonesian Institute of Science and Technology Research, 2023)
The study assessed the effect of capital adequacy requirement on profitability of the Ghana Stock Exchange banks between 2013 and 2018. The analyses were based on the Ghana Stock Exchange secondary statistics. The analyzes specifically assessed trends in the capital adequacy ratios and Ghana Stock Exchange profitability of banks and determine the effect of capital Adequacy Ratio on profitability of listed banks. The study found that the banks' average Capital Adequacy Ratio was (Mean=17.21%) in the time. While the mean Return on Equity (Mean=25.46%) and the mean Return on Asset was found to be (Mean=3.05%). While the profitability was adverse and insignificantly affected by the Capital Adequacy Ratio, they were adverse and small in terms of the Return on Equity, while Capital Adequacy Ratio had a positive and important impact on the Return on Equity. Bank size did not have a major effect on Return on Equity and Return on Asset. For local banks, the mean Capital Adequacy Ratio for international banks was approximately the same. Therefore, the study suggested that businesses continue to operate, if not, to guarantee banks are able to cope with any 'credit crunch' economic recession. Banks can ensure that surplus capital is transformed into investment to maximize investment returns.